Prospective validation study of transorbital Doppler ultrasound imaging for the detection of transient cerebral microemboli. Issue 12 (16th September 2014) - Saedon, M; Dilshad, A; Tiivas, C; Virdee, D; Hutchinson, C E; Singer, D R J; Imray, C H E
Abstract: Background: Transient cerebral microemboli are independent biomarkers of early risk of ischaemic stroke in acute carotid syndromes. Transcranial Doppler imaging (TCD) through the temporal bone is the standard method for detection of cerebral microemboli, but an acoustic temporal bone window for TCD is not available in around one in seven patients. Transorbital Doppler imaging (TOD) has been used when TCD is not possible. The aim of this study was to validate the use of TOD against TCD for detecting cerebral microemboli. Methods: The study included patients undergoing elective carotid endarterectomy; all had confirmed temporal and orbital acoustic windows. Subjects gave written informed consent to postoperative TCD and TOD monitoring, which was performed simultaneously for 30 min by two vascular scientists. Results: The study included 100 patients (mean(s.e.m.) age 72(1) years; 65 men). Microemboli were detected by one or both methods in 40·0 per cent of patients: by TOD and TCD in 24 patients, by TOD alone in ten and by TCD alone in six. For detecting microemboli, TOD had a sensitivity of 80·0 per cent, specificity of 86·1 per cent, positive predictive value of 71·6 per cent and negative predictive value of 91·2 per cent. Bland–Altman analysis revealed no significant bias (bias 0·11 (95 per cent c.i. −0·52 to 0·74) microemboli; P = 0·810) with upper and lower limits of agreement of +6 and −6 microemboli. Conclusion: TOD appears a valid alternative to TCD for detecting microembolic signals in patients with no suitable temporal acoustic window. Abstract : An alternative option